Assessment Of The Utilisation Of Instructional Materials For Teaching Agricultural Science In Senior Secondary Schools In Kaduna State, Nigeria - Karim, Oba Abdulkadir; Ahmed, Abdullahi Hussain; Idi, Danjuma (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This research study was carried out to determine the extent of the utilization of instructional materials for teaching agricultural science in senior secondary schools in Kaduna State, Nigeria. The study was guided by two specific objectives, two research questions and one null hypothesis. Descriptive survey research design was used for the study. The population of the study was fifteen thousand (15,000) agricultural science teachers and students. Three hundred and ninety (390) agricultural science teachers and students were sampled using multistage sampling procedure. The data collected were analysed using frequency counts and percentages to answer the research questions. The null hypothesis was tested using regression analysis at 0.05 level of significance. The result of the study affirmed that utilization of instructional materials have significantly affect teaching of agricultural science in senior secondary schools in Kaduna State. Effectiveness of instructional materials, number of learners per class, resourcefulness of teachers were the factors that affect the use of instructional materials. It was recommended that, school authorities, zonal education offices and government in collaboration with Kaduna State ministry of Education should organize and sponsor training and retraining programmes through workshops, seminars for teachers on utilization of instructional materials for teaching agricultural science in schools.